Analisis Tindak Tutur Ilokusi dalam Lirik Lagu Tertawan Hati Karya Awdella: Kajian Pragmatik - Indah Kusuma Damayanti; Yuniseffendri Yuniseffendri; Titik Indarti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to analyze illocutionary speech acts in the lyrics of the song "Tertawan Hati" by Awdella using a pragmatic approach. The analysis is conducted to explore the meaning, communicative purposes, and pragmatic implications of various illocutionary speech acts found in the lyrics of the song. The research method involves analyzing the lyrics of the song "Tertawan Hati" by identifying and classifying the types of illocutionary speech acts contained in each verse of the song. The results of the analysis will be interpreted in the context of message delivery, expression of emotions, and the overall meaning of the song. Furthermore, this research will consider the influence of culture, social values, and situations in determining the illocutionary speech acts used in the song lyrics. The lyrics of "Tertawan Hati" create a profound and poetic atmosphere with carefully chosen words. The analysis of illocutionary speech acts in these lyrics is expected to help us understand how the singer conveys messages, feelings, and meanings through the medium of music. With a deeper understanding of illocutionary speech acts in song lyrics, we can appreciate the artistic power of music in communicating emotions and meanings to listeners and understand how music can serve as a medium for conveying complex messages about love, longing, and deep emotions.